Heidegger$1 (Bs Contribution to the Understanding of Work-Based Studiess - Gibbs, Paul.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This book seeks to develop the philosophy of Heidegger notion and reflects the growing importance of work based studies which is becoming of special interest to higher education institutions and commercial organisations. The author acknowledges the dominance of the economic discourse of higher education, but in this book he tries to argue that Heidegger offers a phenomenological approach to understanding the diversity to higher education that work based learning can bring. The book offers a structured argument for a phenomenological understanding of both the educational institution and the commercial environment to be considered as workplaces.
Introduction -- Part I: Context -- Chapter 1 Work-Based Learning as a Field of Study -- Chapter 2 Learning as Knowledge of Being-in-the-World -- Chapter 3 Dwelling at Work -- Chapter 4 What is work? A Heideggerian Insight into Work as a Site for Learning -- Chapter 5 Heidegger; Time, Work and the Challenges for University Lead Work-Based Learning -- Part II$1 (BISSUES IN WORK-BASED STUDIES -- Chapter 6 Quality in Work-Based Studies: Not Lost, Merely Undiscovered -- Chapter 7 Assessment and Recognition of Work-Based Learning -- Chapter 8 Learning Agreement$1 (BEntitlements and Evidence in Work-Based Learning -- Chapter 9 A Heideggerian Phenomenology Approach to Higher Education as Workplace: A Consideration of Academic Professionalism -- Chapter 10 Adopting Consumer Time: Potential Issues for Higher Level Work-Based Learning -- Chapter 11 The Concept of Boredom: Its Impact on Work-Based Learning -- Chapter 12 Practical Wisdom and the Workplace Researcher -- Chapter 13 The Recession and the World of Work-Based Studies -- Index.s
Keywords: Education; Phenomenology; Adult education; Education; Professional & Vocational Education; Phenomenology; Lifelong Learning/Adult Education